Changes in muscle quality and biomarkers of neuromuscular junctions and muscle protein turnover following 12 weeks of resistance training in older men - Mastalerz, Andrzej; Hooshmand-Moghadam, Bizhan; Moazamigoudarzi, Shadi; Golestani, Fateme; Hooshmand-Moghadam, Babak; Johne, Monika; Maćkała, Krzysztof; Lorenz, Katarzyna; Maculewicz, Ewelina (Biology of Sport, 2024)
The present study aimed to investigate the effects of 12 weeks of resistance training (RT) on body composition [fat mass(FM), lean body mass(LBM)], muscle quality upper and lower (MQU, MQL), muscle size [cross sectional area (CSA), quadriceps cross-sectional area (QCSA)], biomarkers of neuromuscular junctions [C-terminal agrin fragment (CAF)], and muscle protein turnover [N-terminal peptide (P3NP), 3-methylhistidine (3MH), skeletal muscle specific isoform of troponin T (sTnT)] in older men. Thirty elderly men (age 66.23±0.57 years) were randomly divided into two groups: resistance training group (RT, n =15) and control group (CON, n =15). Participants in RT performed resistance training protocols with the intensity of 60% one-repetition maximum (3×/week, 4 sets of the six exercise circuits). Blood samples were assessed before (pre-test) and after (post-test) a 12-week intervention. The ANCOVA (2×2; group×time; with the baseline variable as the covariate) revealed significant interaction effects; the greater increases for LBM ( P < 0.001), CSA ( P < 0.001), QCSA ( P < 0.001), MQU ( P < 0.05), MQL ( P < 0.01), 3MH ( P < 0.05) were noted in RT than CON, and greater decreases for FM ( P < 0.001) and CAF ( P < 0.001) in RT than CON. No interaction effect was found for P3NP and sTnT. The time effect was found for all variables besides P3NP in RT, but no time effect was revealed in CON. The 12-week RT was an effective strategy for improving the concentrations of neuromuscular junction biomarkers such as 3-MH and CAF in older adults, and may lead to favourable changes in body composition, muscle quality, and muscle size.